Trypanocide treatment of women infected with Trypanosoma cruzi and its effect on preventing congenital Chagas. - Diana L Fabbro; Emmaria Danesi; Veronica Olivera; Maria Olenka Codebó; Susana Denner; Cecilia Heredia; Mirtha Streiger; Sergio Sosa-Estani (Public Library of Science (PLoS), 2014)
With the control of the vectorial and transfusional routes of infection with Trypanosoma cruzi, congenital transmission has become an important source of new cases. This study evaluated the efficacy of trypanocidal therapy to prevent congenital Chagas disease and compared the clinical and serological evolution between treated and untreated infected mothers. We conducted a multicenter, observational study on a cohort of mothers infected with T. cruzi, with and without trypanocidal treatment before pregnancy. Their children were studied to detect congenital infection. Among 354 "chronically infected mother-biological child" pairs, 132 were treated women and 222 were untreated women. Among the children born to untreated women, we detected 34 infected with T. cruzi (15.3%), whose only antecedent was maternal infection. Among the 132 children of previously treated women, no infection with T. cruzi was found (0.0%) (p<0.05). Among 117 mothers with clinical and serological follow up, 71 had been treated and 46 were untreated. The women were grouped into three groups. Group A: 25 treated before 15 years of age; Group B: 46 treated at 15 or more years of age; Group C: untreated, average age of 29.2 ± 6.2 years at study entry. Follow-up for Groups A, B and C was 16.3 ± 5.8, 17.5 ± 9.2 and 18.6 ± 8.6 years respectively. Negative seroconversion: Group A, 64.0% (16/25); Group B, 32.6% (15/46); Group C, no seronegativity was observed. Clinical electrocardiographic alterations compatible with chagasic cardiomyopathy: Group A 0.0% (0/25); B 2.2% (1/46) and C 15.2% (7/46). The trypanocidal treatment of women with chronic Chagas infection was effective in preventing the congenital transmission of Trypanosoma cruzi to their children; it had also a protective effect on the women's clinical evolution and deparasitation could be demonstrated in many treated women after over 10 years of follow up.